2016
DOI: 10.1002/2016ja022435
|View full text |Cite
|
Sign up to set email alerts
|

Flare X‐ray photochemistry of the E region ionosphere of Mars

Abstract: Based on electron density profiles obtained from the Mars Global Surveyor (MGS) we report X‐ray flare responses in the E region ionosphere of Mars during six events that occurred on 28 March and 6 April 2001, 17 and 18 March and 21 April 2003, and 19 February 2005. We have developed a time‐dependent Analytical Yield Spectrum model to calculate a time series of photoionization rate, photoelectron impact ionization rate, photoelectron flux, ion density, electron density, and ionospheric electron content (IEC) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…These observations are in general agreement with the simulations of Lollo et al (), who showed an ~5% ionization enhancement above 155 km, when considering that they did not account for the expanding neutral atmosphere. However, the simulated flare‐induced ion density enhancements by Haider et al (), who predicted ~10 × and 100 × enhancements in O 2 + and CO 2 + density at 200 km, are inconsistent with these observations. These observations indicate that the neutral atmosphere plays an important role in determining the structure of the topside ionosphere after solar flares, and simulations should take this into account, as is done in recent simulations by Xu et al ().…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These observations are in general agreement with the simulations of Lollo et al (), who showed an ~5% ionization enhancement above 155 km, when considering that they did not account for the expanding neutral atmosphere. However, the simulated flare‐induced ion density enhancements by Haider et al (), who predicted ~10 × and 100 × enhancements in O 2 + and CO 2 + density at 200 km, are inconsistent with these observations. These observations indicate that the neutral atmosphere plays an important role in determining the structure of the topside ionosphere after solar flares, and simulations should take this into account, as is done in recent simulations by Xu et al ().…”
Section: Discussionmentioning
confidence: 82%
“…Lollo et al () simulated MGS RO observations with some success, accurately reproducing the large n e enhancement near 110 km, but underpredicting the enhancement between ~80 and 100 km. Recently, Haider et al () simulated the ion production from 80 to 200 km during a solar flare, predicting a ~10–100 × increase in both n e and O 2 + density at 200 km. The authors then predicted integrated electron content values, which were substantially larger than the MGS RO integrated electron content measurements that they compared against.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, ionospheric electron density responses to flares were investigated with MGS and Mars Express data (e.g., Fallows, Withers, & Gonzalez, 2015;Fallows et al, 2015b;Haider et al, 2009;Mahajan et al, 2009;Nielsen et al, 2007). There were also modeling efforts dedicated to reproducing the low-altitude ionospheric responses to flares (e.g., Haider et al, 2012Haider et al, , 2016Lollo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thiemann et al (2015) have recently reported the effect of solar flares on neutral densities and temperatures in the Martian thermosphere. Thiemann et al (2015) have shown that the neutral atmospheric response to a flare is slightly delayed and long lived compared to that of the ionospheric response, which has a time profile similar to the flare (Haider et al, 2016;Lollo et al, 2012;Mendillo et al, 2006). During a flare, the soft X-ray (SXR: 0.1-10 nm) irridiance can increase by 2 orders of magnitude (Woods et al, 2004).…”
Section: Introductionmentioning
confidence: 99%